2019
DOI: 10.3390/w11102027
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of a Large-Scale Cascade Reservoir on the Spawning Conditions of Critical Species in the Yangtze River, China

Abstract: Dam building and reservoir operations alter the downstream hydrological regime, and as a result, affect the health of the river aquatic ecosystem, particularly for large-scale cascade reservoirs. This study investigated the impact of the Gezhouba Reservoir (GR) and the Three Gorges Reservoir (TGR) on the spawning conditions of two critical taxa, i.e., the endemic four major carps and the endangered Chinese sturgeon in the Yangtze River. We analyzed the flow, sediment, and thermal regime in these two taxa spawn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…It is revealed that the impact of climate change has been underestimated in previous studies due to neglecting the meteorological heterogeneity over the catchment (Cai et al 2018, Tao et al 2020, which indicates that the reliance relationships should be used with caution in such large river-reservoir systems. More than one dam is usually constructed on a large river, and their cumulative effects on the downstream RWT and ecosystem have attracted extensive attention (Petesse and Petrere 2012, Cheng et al 2015, Yu et al 2019. This study elaborates the dominance of CDs in the thermal lag upstream of the TGR, and finds that the impact of CDs is rather weak downstream of the TGR, which is in general agreement with the finding of He et al (2020).…”
Section: Discussionsupporting
confidence: 83%
“…It is revealed that the impact of climate change has been underestimated in previous studies due to neglecting the meteorological heterogeneity over the catchment (Cai et al 2018, Tao et al 2020, which indicates that the reliance relationships should be used with caution in such large river-reservoir systems. More than one dam is usually constructed on a large river, and their cumulative effects on the downstream RWT and ecosystem have attracted extensive attention (Petesse and Petrere 2012, Cheng et al 2015, Yu et al 2019. This study elaborates the dominance of CDs in the thermal lag upstream of the TGR, and finds that the impact of CDs is rather weak downstream of the TGR, which is in general agreement with the finding of He et al (2020).…”
Section: Discussionsupporting
confidence: 83%
“…As a result, the low temperature water discharged from the bottom negatively affects the oviposition signal of water-sensitive fish, and ultimately affect the number and quality of oviposition (Caissie, 2006;Ellis and Jones, 2013). Published articles indicate that the water temperature in winter and early spring is highly related to the gonad development of breeding population (Jury, 2012;Yu et al, 2019), reported a significant descending trend for FMCC and CS after TGR operation. Fig.…”
Section: Impact Of Water Conservation On Species Distributionmentioning
confidence: 99%
“…Low temperature, cumulative temperature, and relative temperature difference might delay gonad development of fish and spawning of Chinese sturgeon and Four Major Chinese Carp (Yu et al, 2019). Dam construction has also altered the sediment regimes and influenced river geomorphology, morphology, ecosystem health, and stability (Chang et al, 2017; River Basin are now listed in the China Species Red List which is classified into five threatened categories (Wang and Xie, 2009).…”
Section: Impact Of Water Conservation On Species Distributionmentioning
confidence: 99%